Construction of Nitrogen‐abundant Graphyne Scaffolds via Mechanochemistry‐Promoted Cross‐Linking of Aromatic Nitriles with Carbide Toward Enhanced Energy Storage. Issue 11 (29th December 2022) - Fan, Juntian; Wang, Tao; Thapaliya, Bishnu P.; Li, Meijia; Do‐Thanh, Chi‐Linh; Kobayashi, Takeshi; Popovs, Ilja; Yang, Zhenzhen; Dai, Sheng
Abstract: The 2D graphyne‐related scaffolds linked by carbon–carbon triple bonds have demonstrated promising applications in the field of catalysis and energy storage due to their unique features including high conductivity, permanent porosity, and electron‐rich properties. However, the construction of related scaffolds is still mainly limited to the cross‐linking of CaC2 with multiple substituted aromatic halogens and there is still a lack of efficient methodology capable of introducing high‐concentration heteroatoms within the architectures. The development of alternative and facile synthesis procedures to afford nitrogen‐abundant graphyne materials is highly desirable yet challenging in the field of energy storage, particularly via the facile mechanochemical procedure under neat and ambient conditions. Herein, graphyne materials with abundant nitrogen‐containing species (nitrogen content of 6.9–29.3 wt.%), tunable surface areas (43–865 m 2 g −1 ), and hierarchical porosity are produced via the mechanochemistry‐driven pathway by deploying highly electron‐deficient multiple substituted aromatic nitriles as the precursors, which can undergo cross‐linking reaction with CaC2 to afford the desired nitrogen‐doped graphyne scaffolds efficiently. Unique structural features of the as‐synthesized materials contributed to promising performance in supercapacitor‐related applications, delivering high capacitance of 254.5 F g −1 at 5 mV s −1, attractive rate performance, and good long‐term stability. Abstract : Graphyne materials with abundant nitrogen‐containing species (nitrogen content up to 29.31 wt.%), high surface areas, and hierarchical porosity are produced via the mechanochemistry‐driven pathway by deploying highly electron‐deficient multiple substituted aromatic nitriles as the precursors. Unique structural features of the as‐synthesized materials contribute to promising performance in supercapacitor‐related applications.